1993
DOI: 10.1152/jappl.1993.75.6.2620
|View full text |Cite
|
Sign up to set email alerts
|

Vasoconstrictor properties of rat aorta are diminished by hindlimb unweighting

Abstract: Prolonged bed rest and exposure to weightlessness in humans result in cardiovascular alterations that are characterized by orthostatic intolerance and decreased exercise capacity. Modifications of cardiovascular function have been suggested to be causally related to changes in peripheral vascular reactivity. Rat hindlimb unweighting (HU) was used as an animal model to determine whether prolonged decreases in weight-bearing activity induce changes in vasoreactivity of peripheral arterial vessels. Responses to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
101
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(115 citation statements)
references
References 13 publications
9
101
5
Order By: Relevance
“…These results suggest that the NE-induced contraction of the rabbit basilar artery is induced mainly through activation of ␣ 1 -adrenergic receptors. Contractile responses to pheyleprine have been shown to decrease in the isolated aorta from rats exposed to hind-limb unloading [12], but not in leg vasculature of humans during HDT [18]. In the present study, phenylephrine-induced contraction of the rabbit basilar artery was smaller in the HDT group than in the control group, suggesting that activity of ␣ 1 -adrenergic receptors is related to the mechanism of decreased NE response.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…These results suggest that the NE-induced contraction of the rabbit basilar artery is induced mainly through activation of ␣ 1 -adrenergic receptors. Contractile responses to pheyleprine have been shown to decrease in the isolated aorta from rats exposed to hind-limb unloading [12], but not in leg vasculature of humans during HDT [18]. In the present study, phenylephrine-induced contraction of the rabbit basilar artery was smaller in the HDT group than in the control group, suggesting that activity of ␣ 1 -adrenergic receptors is related to the mechanism of decreased NE response.…”
Section: Discussioncontrasting
confidence: 51%
“…The effects of simulated microgravity on vascular responses to vasoactive agents have been investigated in rats exposed to hind-limb unloading or tail suspension. Delp and co-workers [12] showed that the contractile responses of isolated rat aorta to vasoconstrictors such as KCl, NE, phenylephrine, arginine vasopressin, and CaCl 2 were attenuated by hind-limb unloading. Purdy and colleagues [16] demonstrated that the NE-induced contraction of rat carotid and femoral arteries, as well as the aorta, was also reduced by 20 d of hind-limb unloading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, impairments of macro-and microcirculation are also involved in this downregulation (1). On rodent models, studies were carried out and showed that simulated weightlessness has negative effects on structural (13) and functional properties (8,14) of vasculature. Another part of this downregulation is an alteration of equilibrium system (40).…”
Section: Why Countermeasure Had No Effect On Orthostatic Responsementioning
confidence: 99%
“…HU rats demonstrate many cardiovascular adaptations characteristic of cardiovascular deconditioning in humans, including a reduced exercise capacity (17, 39), orthostatic hypotension (29, 55), and a diminished capacity to elevate PVR (31, 57). This diminished ability to elevate PVR has been shown to be related to reductions in vasoconstrictor responsiveness of a number of conduit arterial segments (14,16,40,41,43,59) and skeletal muscle arterioles (13) from HU rats. However, because ϳ20% of the increase in PVR during orthostasis normally occurs as a result of vasoconstriction in splanchnic organs (42), a diminished constrictor response within the splanchnic vasculature could potentially be an underlying mechanism for orthostatic hypotension.…”
mentioning
confidence: 99%